Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/lary.26806
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the laryngopharyngeal reflux treatment algorithm: Evaluating an alternate empiric dosing regimen and considering up‐front, pH‐impedance, and manometry testing to minimize cost in treating suspect laryngopharyngeal reflux disease

Abstract: 4. Laryngoscope, 127:S1-S13, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…These results were comparable to a similar study conducted by Carroll et al, which demonstrated that a once-daily, 40 mg omeprazole and once nightly, 300 mg ranitidine (QD/QHS) dosing improved the majority (67%) of patients who presented with signs and symptoms of LPR and ultimately responded to empiric acid suppression. 19 Although similar results have been demonstrated in studies of Belafsky et al 12 and Bilgen et al 32 but these studies used pH monitoring for diagnosis of LPR and used only PPIs in the treatment of LPR. pH monitoring was not done in our study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These results were comparable to a similar study conducted by Carroll et al, which demonstrated that a once-daily, 40 mg omeprazole and once nightly, 300 mg ranitidine (QD/QHS) dosing improved the majority (67%) of patients who presented with signs and symptoms of LPR and ultimately responded to empiric acid suppression. 19 Although similar results have been demonstrated in studies of Belafsky et al 12 and Bilgen et al 32 but these studies used pH monitoring for diagnosis of LPR and used only PPIs in the treatment of LPR. pH monitoring was not done in our study.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies demonstrated clinically evident benefits in the treatment but some studies did not report any clinical benefits of the use of H2RA in LPR. [19][20][21][22] There are very few studies that have studied the effects of combination therapy with PPI and H2RA (BBF/HS dose) in patients with LPR. The objective of this study was to evaluate once-daily, 40 mg pantoprazole and once nightly, 300 mg ranitidine (BBF/HS) dosing as an alternative empiric regimen in the management of LPR.…”
Section: Introductionmentioning
confidence: 99%
“…In less than 50% of cases, these complaints are associated with gastro‐oeosophageal reflux disease (GERD) symptoms such as heartburn and regurgitation. LPR‐related symptoms impair quality of life and require prolonged treatment, which is associated with a significant cost …”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the empirical therapeutic trial based on proton pump inhibitors (PPIs) was proposed as the main cost-effective approach to treat and support the LPR diagnosis [71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Nowadays, this approach is increasingly challenged for many reasons [64,75]. First, PPIs are suspected to have short-and long-term side effects (Table 3) that support the PPI prescription only in patients with an identified acid reflux disease and for the shorter duration [64].…”
Section: Cost-effective Empirical Approachmentioning
confidence: 99%